USER PERCEPTIONS OF THE QUALITY OF THE PEDULILINDUNGI APPLICATION BASED ON THE DIMENSIONS OF ELECTRONIC SERVICE QUALITY (E-SERVICE QUALITY) DURING THE COVID-19 PANDEMIC - Bianca, Gabriela; Sari, Kurnia; Junadi, Purnawan (Journal of Indonesian Health Policy and Administration, 2023)
The use of a contact tracing application is one of the efforts made to overcome the global COVID-19 pandemic with an increasing number of cases. The contact tracing application used in Indonesia is PeduliLindungi which is one of the requirements for accessing public areas, which was initially applied to the Java-Bali region. However, in its use, there are still challenges that affect the quality of electronic services. This study aims to analyze user perceptions of the service quality of the PeduliLindungi application based on the E-Servqual dimension. The method used is observational with a quantitative approach using a cross-sectional design. The results showed that overall, the user's perception of the quality of the PeduliLindungi application was good with positive ratings on the service quality dimensions of the PeduliLindungi application. The dimensions that have a significant relationship to the user's perception of the quality of the PeduliLindungi (ESQ) application are the dimension of user experience (EXP) and user trust (TRU). The dimension of reliability (REL), responsiveness (RES), ease of use (EOU), privacy (PRI), system availability (SA), application design (WD), and information quality (IQ) do not have a significant relationship to user perceptions of the quality of the PeduliLindungi (ESQ) application. Suggestions that can be given are to improve and improve the system and technical functions and improve security for user data.